Bilateral thyrolinguofacial trunk: unusual and rare branching pattern of external carotid artery - Baxla, Monica (Anat Cell Biol, 2018)
Prior knowledge of arterial supply to the head and neck is of substantial importance for well-planned surgeries involving the concerned region. We are reporting an unusual and rare variation in the branching pattern of external carotid artery in a 60-year-old female cadaver. A common trunk known as thyrolinguofacial trunk, originating from the anterior surface of the external carotid artery (right and left) giving of superior thyroid artery and a linguofacial trunk during a routine neck dissection. The linguofacial trunk then divided into a lingual and a facial artery. Vascular abnormalities are usually detected either on the dissection table or by the radiologists during imaging or accidently during surgeries leading to serious consequences.